CASING FAILURE ANALYSIS IN STEAM INJECTION WELL OPERATIONS USING FINITE ELEMENT METHODS - BHARADWAJ, ABHILASH MURALIDHAR (2016)
Steam injection is a successful method to increase heavy-oil production. But the casing failure rates in steam injection wells are also an important concern. Severe thermal stresses causing casing failures have been reported in the past leading to downtime, high cost or low rate of production. Failures such as buckling, internal diameter restriction, joint pull out, etc., are common occurrences, especially, inpoorly cemented sections of the well. The casings are prone to thermal fatigue due to cyclic steam injection operations. In other cases, part of the casing section is wornout either uuc iu Jiill iuul uunicu;i ui utlici dillling operations. Such sections become vulnerable to failure during high pressure/high temperature conditions.